(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Improving the educational process is determined by the desire of teachers to activate the knowledge and interests of students. The essence of activating cognitive interests is to organize an educational activity in which the student acquires the basic skills of acquiring knowledge and learns to acquire knowledge independently on this basis.